Optimization Of Mixing Chamber Design on Steam Ejector at Geothermal Power Plant Based on CFD Simulation - Sendi Salman Rusdan; Yanti Suprianti (Journal of Green Science and Technology, 2025)
The initial generation capacity of 30 MW at the Geothermal Power Plant (GPP) decreased to 11.88 MW due to reduced steam supply from production wells. This mismatch between the original system design and current operating conditions affected components such as the steam ejector, which experienced a reduction in motive steam flow from 1.96 kg/s to 1.66 kg/s. As a result, the mixing chamber became inefficient in entraining flow of non- condensable gases (NCG), causing suboptimal pressure ratios (P3/P5), turbulence, and backflow. This study aims to redesign the mixing chamber of the steam ejector to enhance the extraction NCG. Using compressible flow theory and CFD simulation with Ansys Fluent 2025R1, the redesigned geometry improved the entrainment ratio from 0.27 to 0.31 and increased the NCG suction rate from 0.45 kg/s to 0.52 kg/s. The pressure ratio P3/P5 rose from 0.04 to 0.07, approaching optimal conditions. Further analysis revealed that under increased motive flow (1.687 kg/s), the ejector achieved an entrainment ratio of 0.32, and under lowered condenser pressure (8.1 kPa), the entrainment reached 0.34. These two optimal conditions demonstrate the redesigned chamber’s adaptability under varied operational scenarios. The performance improvement contributed to an additional power output of 41.68 kWh, approaching the plant’s installed capacity and improving system reliability. From economic perspective, the optimization is also feasible, yielding a net present value (NPV) of Rp6.46 million and demonstrating high profitability and practical applicability.